2018
DOI: 10.1101/432278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship between ecological stoichiometry and community diversity of plant ecosystems in the upper reaches of the Tarim River, China

Abstract: Relationship between ecological stoichiometry and community diversity of plant3 ecosystems in the upper reaches of the Tarim Abstract 33 Aim Although it is commonly proposed that nutrient cycling can impact plant 34 community diversity, this relationship has not been fully examined in arid and 35 semi-arid zones. Here, we expand on the framework for evaluating the relationship 36 between biodiversity and ecological stoichiometry by scaling up from the level of the 37 community. 38 Location The upper reaches of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The tugai forests thus constitute a highly threatened ecosystem 52 . Plant species diversity and richness are considered to be the primary objectives of successful restoration 53 . Our study demonstrates that the plant diversity indices in classes 1 and 2 were higher than those in classes 4 and 5 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The tugai forests thus constitute a highly threatened ecosystem 52 . Plant species diversity and richness are considered to be the primary objectives of successful restoration 53 . Our study demonstrates that the plant diversity indices in classes 1 and 2 were higher than those in classes 4 and 5 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We highlighted the lack of ES studies in terrestrial ecosystems in a previous review to evaluate topics such as the GRH, relationships of elemental stoichiometry with trophic web function and species composition in ecosystems and communities (Sardans et al, 2012). Several recent studies have provided further evidence that changes in the N:P ratios of media (water or soil) or food affect the structure of food webs in terrestrial ecosystems (Fanin et al, 2013;Zechmeister-Bolstenstren et al, 2015;Paseka and Grunberg, 2019) and other studies have observed this link in aquatic ecosystems (Plum et al, 2015;Sitters et al, 2015;Lee et al, 2017;Zhao et al, 2018b;Nhu et al, 2019). Shifts in organismic stoichiometry throughout trophic webs due to changes in excreted stoichiometry and/or resource use (nutrients, light, water) have provided new insights into the changes in community composition, dynamics, and functionality in freshwater and marine ecosystems (Glibert et al, 2011;Hillebrand and Lehmpfuhl, 2011;Hessen et al, 2013;Plum et al, 2015;Galbraith and Martiny, 2015;Vanni and McIntyre, 2016;Filipiak, 2016;Moorthi et al, 2017;Vanderploeg et al, 2107;Branco et al 2018;Moody et al, 2018;Mousing et al, 2018;Prater et al, 2018;Spilling et al, 2019;Tanioka and Matsumoto, 2019).…”
Section: Effects Of Stoichiometry On Ecosystem Structure and Functionmentioning
confidence: 97%